Culturally-adapted behavioral intervention to improve colorectal cancer screening uptake among foreign-born South Asians in New Jersey: the Desi Sehat trial. Issue 4 (19th May 2021) - Manne, Sharon L.; Islam, Nadia; Frederick, Sara; Khan, Usman; Gaur, Sunanda; Khan, Anam
ABSTRACT: Objectives: Colorectal cancer (CRC) is the third most common cancer among Americans of South Asian (SA) descent and is a significant public health concern in SA communities. Rates of screening compliance among foreign-born SAs are very low. The goal of this study was to report on the development, acceptability, and preliminary impact of a culturally-targeted 1:1 intervention delivered in English, Hindi, and Urdu, called Desi-Sehat. Design: Ninety-three foreign-born SAs between the ages of 50 and 75 were recruited using community-based organization methods. Participants completed a baseline survey, participated in a 1:1 session with a community health educator, and a follow-up survey was administered four months after the baseline. Results: The acceptance rate was moderate (52.8%). Attendance at the intervention session was high. More than half of the population did not complete the follow-up survey (58.7%). Participant evaluations of the intervention were high. Intent-to-treat analyses indicate a 30% four month follow-up CRC screening uptake. There were significant increases in knowledge and significant reductions in perceived barriers to screening, worry about CRC screening tests, and worry about CRC. Effect sizes for significant changes were in the medium to large range. Conclusions: Desi Sehat was a well-evaluated and participation in the session was high, participant knowledge significantly increased, and screening barriers, worry about CRC, and worry about CRC screening tests declined significantly. Future studies should focus on enhancing recruitment and retention and include a randomized control design.